The #MeToo Movement as a Global Learning Moment - Regulska, Joanna (International Higher Education, 2018)
This article places the #MeToo movement within the context of global learning. Given the global nature of sexual harassment, sexual assault, and violence against women, it asks what responsibilities we have as international educators. It raises numerous questions that can be utilized as teaching tools—and it proposes that institutions rethink internationalization strategies and seize this moment of opportunity to create an inclusive and diverse environment conducive to advancing intercultural and intracultural understanding.